Atoms and cells - Bender, Lionel (New York : Gloucester Press, 1990)
Text and photographs introduce microscopic plant and animal life, viruses, microspores, and other forms of life which can only be viewed through a microscope.
Includes index.
Booklist
School Library Journal
6.5
3-6
Keywords: Microorganisms -- Juvenile literature; Cells -- Juvenile literature; Microscopy -- Juvenile literature; Biomolecules -- Juvenile literature; Microorganisms; Cells; Microscopy; Microorganisms; Cells; Microscope and microscopy